2022
DOI: 10.1002/asia.202200624
|View full text |Cite
|
Sign up to set email alerts
|

Cu‐Based Organic‐Inorganic Composite Materials for Electrochemical CO2Reduction

Abstract: Electrochemical CO2 reduction reaction (CO2RR) is an attractive pathway to convert CO2 into value‐added chemicals and fuels. Copper (Cu) is the most effective monometallic catalyst for converting CO2 into multi‐carbon products, but suffers from high overpotentials and poor selectivity. Therefore, it is essential to design efficient Cu‐based catalyst to improve the selectivity of specific products. Due to the combination of advantages of organic and inorganic composite materials, organic‐inorganic composites ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 192 publications
0
4
0
Order By: Relevance
“…209 Recently, a new clean strategy to reduce greenhouse gas emissions by transforming atmospheric CO 2 into useable chemicals and fuels may become the driving force towards carbon neutrality. 209–212 The large-scale implementation of ocean-based carbon dioxide removal (CDR) technologies coupled with this new promising strategy to reduce CO 2 emission has enormous potential to mitigate climate change and prevent further ocean acidification.…”
Section: Summary and Future Researchmentioning
confidence: 99%
“…209 Recently, a new clean strategy to reduce greenhouse gas emissions by transforming atmospheric CO 2 into useable chemicals and fuels may become the driving force towards carbon neutrality. 209–212 The large-scale implementation of ocean-based carbon dioxide removal (CDR) technologies coupled with this new promising strategy to reduce CO 2 emission has enormous potential to mitigate climate change and prevent further ocean acidification.…”
Section: Summary and Future Researchmentioning
confidence: 99%
“…For instance, as one of the most common reactions in thermal catalysis, typical conditions for methanol synthesis using CO 2 are at 100 bar and 250 °C [23]. The low number of active sites on the photocatalytic material surface makes it difficult to efficiently adsorb and activate stable CO 2 molecules, resulting in actual photocatalytic CO 2 reduction efficiencies well below the standards of commercialization, accompanied with product yields at μmol•g -1 •h -1 level [24][25][26]. Electrocatalytic CO 2 reduction (Figs.…”
Section: Strategies Of Co 2 Utilization and Storagementioning
confidence: 99%
“…This type of material is also frequently used in the modification of Cu-based catalysts. Among these, Cu-MOFs and their derivative catalytic materials have played a significant role in CO 2 RR reactions [24,25]. Research has found that Cu-MOFs and their derivatives exhibit an excellent selectivity and high performance for C2 products.…”
Section: Introductionmentioning
confidence: 99%